Strong Equality Co-Neighborhood Domination in Graphs - Sahib Sh. Kahat (Genius Journals, 2022)
In this paper, SENDS in graphs is defined. Some properties of SENDS are determined for some special graphs
Keywords: Strong co-neighborhood dominating set; Strong co-neighborhood domination number